Ocrelizumab-induced colitis and cytomegalovirus infection and their disadvantageous interaction with underlying multiple sclerosis - Lieb, Sabine; Heni, Maria; Rauschenberg, Sophie; Lange, Kay; Feisthammel, Juergen; Bläker, Hendrik; Wiegand, Johannes (Zeitschrift für Gastroenterologie, 2023)
Ocrelizumab is a humanized monoclonal antibody against the B-lymphocyte antigen CD20 and the only approved treatment option in primary progressive multiple sclerosis. Herpesvirus-related infections like cytomegalovirus (CMV) infections are common in patients receiving ocrelizumab, whereas gastrointestinal side effects with inflammatory bowel disease (IBD) like esophagitis or colitis are very rare. This case report describes the challenging clinical, endoscopic, and histologic features of an ocrelizumab-induced colitis overlapping with CMV infection and their disadvantageous interaction with the underlying multiple sclerosis.
Keywords: ocrelizumab toxicity; ocrelizumab tolerability; monoclonal CD20 antibody; inflammatory bowel disease; CMV-colitis; gastrointestinal side effects